R & D Capital, Rate of Return on R & D Investment and Spillover of R & D in Japanese Manufacturing Industries - Goto, Akira; Suzuki, Kazuyuki (The Review of Economics and Statistics, 1989)
Akira Goto, Kazuyuki Suzuki, R & D Capital, Rate of Return on R & D Investment and Spillover of R & D in Japanese Manufacturing Industries, The Review of Economics and Statistics, Vol. 71, No. 4 (Nov., 1989), pp. 555-564